Simulation of real time predictive system for a production line - Ramanathan Anbalagan (2009)
Using a data acquisition and control software, this project involves the development of an emulation program to enable centralised interface, control and emulation of a production line model through a host computer. The production Line model here represents the Surface Mount Technology (SMT) Line model for PCB assembly.